Recurrence of pseudomyxoma peritonei after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 2 (27th September 2018) - Mercier, F.; Dagbert, F.; Pocard, M.; Goéré, D.; Quenet, F.; Wernert, R.; Dumont, F.; Brigand, C.; Passot, G.; Glehen, O.; ,
Abstract : Background: Pseudomyxoma peritonei (PMP) is a rare clinical condition characterized by mucinous ascites, typically related to appendiceal or ovarian tumours. Current standard treatment involves cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC), but recurrences occur in 20–30 per cent of patients. The aim of this study was to define the timing and patterns of recurrence to provide a basis for modifying follow‐up of these patients. Methods: This observational study examined a prospectively developed multicentre national database (RENAPE working group) to identify patients with recurrence after optimal CRS and HIPEC for PMP. Postoperative complications, long‐term outcomes and potential prognostic factors were evaluated. Results: Of 1411 patients with proven PMP, 948 were identified who had undergone curative CRS and HIPEC. Among these patients, 229 first recurrences (24·2 per cent) were identified: 196 (20·7 per cent) occurred within the first 5 years (early recurrence) and 30 (3·2 per cent) occurred between 5 and 10 years. Three patients developed a first recurrence more than 10 years after the original treatment. The mean(s.d.) time to first recurrence was 2·36(2·21) years. Preoperative chemotherapy and high‐grade pathology were significant factors for early recurrence. Overall survival for the entire group was 77·9 and 63·1 per cent at 5 and 10 years respectively. The principal site of recurrence was the peritoneum. Conclusion: Recurrence of PMP was rare after 5 years and exceptional after 10 years. Abstract : Recurrence of pseudomyxoma peritonei (PMP) following completeness of cytoreduction (CC)‐0 or CC‐1 and hyperthermic intraperitoneal chemotherapy (HIPEC) may occur in up to 25% of patients. Recurrence rates were 13·3% between 5 and 10 years and 1·6% after 10 years. High‐grade pathology was a significant risk factor for early recurrence. 85% of recurrences within 5 years